Strategic plan for Bread Factory Commissary - Marbas, Sundee F. (School of Management, University of the Philippines Mindanao, 2011)
The bakery industry in the Philippines is highly fragmented with a large number of small family owned neighborhood bakeries. Trade and government sources comment that the industry has tens of thousands of small bakeries; estimated at well over 20,000 operational businesses. The industry has come under immense pressure from high and increasing production costs including wheat flour cost. This has led to a significant shrinkage in the number of businesses operating in the industry because marginal businesses have closed their bakery operations. The local economy of Region XI is continually growing and both local and international bakery brands are entering the local market. This paper will outline a strategic plan for Bread Factory Commissary on how to achieve a sustained competitive advantage and growth of the company amidst the competition and the pertinent obstacles facing the bakery industry. It is difficult to be successful in business nowadays without a roadmap for success. A strategic plan helps to provide direction and focus. It points to specific results that are to be achieved and establishes a course of action for achieving them. Fred R. David defines Strategic Management as the art and science of formulating, implementing, and evaluating cross-functional decisions that enable an organization to achieve its objectives. The analytical framework applied on this paper is the Strategic Management process by Fred R. David. This process involves three (3) stages: Strategy Formulation, Strategy Implementation and Strategy Evaluation. Strategy formulation includes developing a vision and mission, identifying an organization's external opportunities and threats, determining internal strengths and weaknesses, establishing long-term objectives, generating alternative strategies, and choosing particular strategies to pursue.